2021
DOI: 10.1371/journal.pone.0251665
|View full text |Cite
|
Sign up to set email alerts
|

Required warfarin dose and time in therapeutic range in patients with diagnosed Nonalcoholic Fatty Liver Disease (NAFLD) or Nonalcoholic Steatohepatitis (NASH)

Abstract: Warfarin has been widely used to treat thromboembolism. The effect of nonalcoholic fatty liver disease (NAFLD) or nonalcoholic steatohepatitis (NASH), on warfarin dosing remains unknown. This study aims to examine the effects of NAFLD/NASH on the average daily dose (ADD) of warfarin and the time in therapeutic range (TTR). This is a retrospective study utilizing an administrative data. We included patients with at least 2 months of warfarin dispensing and two subsequent consecutive INR measures. The ADD of war… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 63 publications
1
5
0
Order By: Relevance
“…59 The average therapeutic daily dose of warfarin (S-warfarin), another CYP2C9 substrate, was not significantly different between NAFLD patients with and without cirrhosis compared with non-NAFLD control groups in two separate studies. 65,66 This is in line with nonsignificant changes in protein levels of CYP2C9 (involved in warfarin metabolism) and CYP4F2 (responsible for catabolism of vitamin K and associated with interindividual variability in warfarin response) in patients with non-cirrhotic NAFLD compared with non-NAFLD individuals with similar BMI. 39 Despite observing no change in warfarin daily dose relative to the control group, Zhang et al 66 reported a lower international normalized ratio to warfarin dose ratio in NAFLD (cirrhosis status not reported), suggesting potential NAFLDmediated alterations in vitamin K regulation or other pharmacodynamic factors that may impact warfarin response.…”
Section: Impact Of Nafld On Clinical Pharmacokineticssupporting
confidence: 66%
See 1 more Smart Citation
“…59 The average therapeutic daily dose of warfarin (S-warfarin), another CYP2C9 substrate, was not significantly different between NAFLD patients with and without cirrhosis compared with non-NAFLD control groups in two separate studies. 65,66 This is in line with nonsignificant changes in protein levels of CYP2C9 (involved in warfarin metabolism) and CYP4F2 (responsible for catabolism of vitamin K and associated with interindividual variability in warfarin response) in patients with non-cirrhotic NAFLD compared with non-NAFLD individuals with similar BMI. 39 Despite observing no change in warfarin daily dose relative to the control group, Zhang et al 66 reported a lower international normalized ratio to warfarin dose ratio in NAFLD (cirrhosis status not reported), suggesting potential NAFLDmediated alterations in vitamin K regulation or other pharmacodynamic factors that may impact warfarin response.…”
Section: Impact Of Nafld On Clinical Pharmacokineticssupporting
confidence: 66%
“…When controlled for CYP2C9 genotype, the plasma metabolite‐to‐parent ratio of losartan (a CYP2C9 substrate) was markedly lower in adolescents with NASH compared with a healthy cohort, although the corresponding ratio evaluated using urine samples was not affected by NAFLD disease status 59 . The average therapeutic daily dose of warfarin (S‐warfarin), another CYP2C9 substrate, was not significantly different between NAFLD patients with and without cirrhosis compared with non‐NAFLD control groups in two separate studies 65,66 . This is in line with nonsignificant changes in protein levels of CYP2C9 (involved in warfarin metabolism) and CYP4F2 (responsible for catabolism of vitamin K and associated with interindividual variability in warfarin response) in patients with non‐cirrhotic NAFLD compared with non‐NAFLD individuals with similar BMI 39 .…”
Section: Impact Of Nafld On Clinical Pharmacokineticsmentioning
confidence: 60%
“…Anticoagulants like warfarin are frequently indicated in these patients to prevent thromboembolic events. Patients with NAFLD along with valvular disease are seen to require higher doses of warfarin and even then, they are less likely to stay in the therapeutic range as compared to patients without NAFLD [ 44 ].…”
Section: Cardiovascular Diseasementioning
confidence: 99%
“…Furthermore, the activity of dabigatran has been related to a reduction in high-fat diet-induced weight gain [ 48 ]. Interestingly, possible interactions among anticoagulant activity, weight gain/obesity, and NAFLD were recently reported in humans by Wen et al [ 49 ]. Lower average warfarin daily dosage and shorter time in the therapeutic range were found in patients diagnosed with NAFLD/NASH [ 49 ].…”
Section: Hypercoagulability and Anticoagulation In Nafldmentioning
confidence: 99%
“…Interestingly, possible interactions among anticoagulant activity, weight gain/obesity, and NAFLD were recently reported in humans by Wen et al [ 49 ]. Lower average warfarin daily dosage and shorter time in the therapeutic range were found in patients diagnosed with NAFLD/NASH [ 49 ]. Notwithstanding, this anticoagulation in patients with NAFLD has been poorly investigated.…”
Section: Hypercoagulability and Anticoagulation In Nafldmentioning
confidence: 99%